Correlation of Left Atrial Appendage Ejection Velocities with the CHADS2 and CHA2DS2‐VASc Scores. Issue 8 (5th April 2016) - Clark, Craig B.; Telles Garcia, Nelson A.; Hackett Renner, Catherine; Ryan, Sarah M.
Abstract : Background: In patients with atrial fibrillation or flutter, a left atrial appendage ejection velocity measured via transesophageal echocardiography equal to or less than 40 cm/sec has been shown to correlate with an increased risk of developing left atrial appendage thrombus while velocities greater than 40 cm/sec are at lower risk. The CHADS2 and CHA2DS2‐VASc scores calculated from clinical variables have been developed to risk stratify patients with atrial fibrillation/flutter in regard to the need for anticoagulation. This study was designed to assess whether a relationship exists between left atrial appendage ejection velocities and the respective CHADS2 and CHA2DS2‐VASc scores, and whether this relationship is affected by the presence of atrial fibrillation or atrial flutter. Methods: A retrospective chart review was performed on patients in the last 5 years who had undergone a transesophageal echocardiogram in which LAA velocity was measured. Once these patients were identified, relevant clinical information allowing for the calculation of the CHADS2 and CHA2DS2‐VASc scores was also extracted from the medical record. Results: Data from a total of 151 patients were included in the study. A statistically significant correlation between LAA velocity and CHADS2 score (P = 0.942) or between LAA velocity and CHA2DS2‐VASc scores (P = 0.723) was not found. Conclusions: We could not identify a relationship between either the CHADS2 or CHA2DS2‐VASc scores and LAA velocities. This was true regardless of whether patients were in sinus rhythm or AF at the time of the TEE. While reduced LAA velocities increase the risk of LAA thrombus, the development of stroke in patients with AF is secondary to a complex interplay of multiple clinical variables.